2015
DOI: 10.1037/neu0000164
|View full text |Cite
|
Sign up to set email alerts
|

Betting on DBS: Effects of subthalamic nucleus deep brain stimulation on risk taking and decision making in patients with Parkinson’s disease.

Abstract: Objective Concerns persist that deep brain stimulation (DBS) for Parkinson’s disease (PD) increases impulsivity and/or induces excessive reward-seeking. We report here the performance of PD patients with implanted subthalamic nucleus electrodes, with stimulation on and off, on three laboratory tasks of risk-taking and decision-making. They are compared to PD patients maintained on medication and normal control subjects. Methods and Results In the Game of Dice Task, a test of “risky” decision-making, PD patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 74 publications
1
29
1
Order By: Relevance
“…Moreover, this effect was more pronounced in the DBS ON condition versus OFF (Brandt et al ., 2015). A study by Boller and colleagues corroborated these findings, demonstrating higher risk behavior in the DBS off condition versus DBS on.…”
Section: Impulsivity and The Stnmentioning
confidence: 98%
“…Moreover, this effect was more pronounced in the DBS ON condition versus OFF (Brandt et al ., 2015). A study by Boller and colleagues corroborated these findings, demonstrating higher risk behavior in the DBS off condition versus DBS on.…”
Section: Impulsivity and The Stnmentioning
confidence: 98%
“…2 most studies found PD patients, both on and off medication, to be significantly impaired compared to HCs. Few studies focused specifically on the role of dopaminergic medication, but the possible impact hereof on decision-making was emphasized by several authors [23,28,29].…”
Section: Methodsmentioning
confidence: 99%
“…Some studies used a repeated measures approach when testing patients on/off medication [22,24,30], while others tested different subjects for the on and off medication condition [31,32]. Moreover, in some studies patients were tested several times, while HCs were only tested once [23,24]. This could potentially be problematic and result in test-retest effects confounding the results.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between DBS and ICD is controversial . Bilateral STN‐DBS was found to negatively affect decision‐making during acute postoperative stages, to improve decision‐making under risk, or to be unaffected . STN‐DBS has been identified as an independent risk factor for binge eating, to induce “punding,” and worsen ICD .…”
Section: Introductionmentioning
confidence: 99%